2003
DOI: 10.2307/3557069
|View full text |Cite
|
Sign up to set email alerts
|

Calibrated Radiocarbon Dating at Keatley Creek: The Chronology of Occupation at a Complex Hunter-Gatherer Village

Abstract: This paper provides an analysis of radiocarbon dates acquired during earlier and recent field seasons at the Keatley Creek site, southern British Columbia. Results indicate that early occupations predating 1900 cal. B.P. occurred, but were not likely associated with population aggregation and large housepits. The aggregated village appears to have emerged by approximately 1700 cal. B.P. and was abandoned at approximately 800 cal. B.P. A break in the occupational sequence is recognized at 1450-1350 cal. B.P. an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
(12 reference statements)
0
24
0
Order By: Relevance
“…Recent research by Prentiss et al (2003Prentiss et al ( , 2005a has offered an alternative dating sequence for the rim midden deposits of Housepit 7 and the Keatley Creek village. New dating of early features suggests that Housepit 7 and likely the entire aggregated village existed between 1614 and 747 cal.…”
Section: The Keatley Creek Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Recent research by Prentiss et al (2003Prentiss et al ( , 2005a has offered an alternative dating sequence for the rim midden deposits of Housepit 7 and the Keatley Creek village. New dating of early features suggests that Housepit 7 and likely the entire aggregated village existed between 1614 and 747 cal.…”
Section: The Keatley Creek Sitementioning
confidence: 99%
“…1) has been at the center of many discussions regarding the emergence of complex hunter-gatherers featuring socio-economic status inequality (Hayden, 1997a). The site offers one of North America's best examples of a complex hunter-gatherer community (Cannon, 1999) as it is large (over 115 house depressions), there is a long occupation span, and preservation conditions for organic artifacts are extremely good (Hayden, 1997b;Prentiss et al, 2003). Hayden's extensive excavations at the site (and other tangential studies [e.g., Schulting, 1995]) have suggested that the large aggregate winter village was probably occupied by ranked corporate groups that controlled access to a variety of resources possibly including fishing places and quarries.…”
Section: The Keatley Creek Sitementioning
confidence: 99%
“…Although there are debates concerning the founding and occupation sequence of these large village sites, they were definitely aggregated and concentrated by ca. 1600-1000 B.P, and perhaps earlier (Hayden, 2005;Kuijt and Prentiss, 2004;Lenert, 2001;Morin et al, 2008;Prentiss et al, 2003Prentiss et al, , 2005Prentiss et al, , 2007Prentiss et al, , 2008. However, the Mid-Fraser region was largely depopulated associated with decline of large village sites after ca.…”
Section: Natural and Cultural Settingsmentioning
confidence: 90%
“…Thus, most of this information is based on the total number of housepits derived from our recent work (Morin et al, 2008) in addition to Stryd and Hills (1972) who conducted an initial archaeological survey in the Mid-Fraser region. The database also needs an updated Mid-Fraser chronology, since 14 C dating at the Keatley Creek and Bridge River sites has been refined quite recently (Hayden, 2000b;Prentiss et al, 2003Prentiss et al, , 2008. Based on new and original archaeological reports, we have modified the site attributes, such as site typology and dating, as needed.…”
Section: Datasets and Analytical Techniquesmentioning
confidence: 98%
See 1 more Smart Citation